Affective lability mediates the association between childhood trauma and suicide attempts, mixed episodes and co-morbid anxiety disorders in bipolar disorders. Issue 5 (29th November 2016) - Aas, M.; Henry, C.; Bellivier, F.; Lajnef, M.; Gard, S.; Kahn, J.-P.; Lagerberg, T. V.; Aminoff, S. R.; Bjella, T.; Leboyer, M.; Andreassen, O. A.; Melle, I.; et al.
Abstract : Background: Many studies have shown associations between a history of childhood trauma and more severe or complex clinical features of bipolar disorders (BD), including suicide attempts and earlier illness onset. However, the psychopathological mechanisms underlying these associations are still unknown. Here, we investigated whether affective lability mediates the relationship between childhood trauma and the severe clinical features of BD. Method: A total of 342 participants with BD were recruited from France and Norway. Diagnosis and clinical characteristics were assessed using the Diagnostic Interview for Genetic Studies (DIGS) or the Structured Clinical Interview for DSM-IV Axis I disorders (SCID-I). Affective lability was measured using the short form of the Affective Lability Scale (ALS-SF). A history of childhood trauma was assessed using the Childhood Trauma Questionnaire (CTQ). Mediation analyses were performed using the SPSSprocess macro. Results: Using the mediation model and covariation for the lifetime number of major mood episodes, affective lability was found to statistically mediate the relationship between childhood trauma experiences and several clinical variables, including suicide attempts, mixed episodes and anxiety disorders. No significant mediation effects were found for rapid cycling or age at onset. Conclusions: Our data suggest that affective lability may represent a psychological dimension that mediates the association between childhood traumatic experiences and the risk of a more severe or complex clinical expression of BD.